Paediatric nasal polyps in cystic fibrosis. (21st June 2016) - Mohd Slim, Mohd Afiq; Dick, David; Trimble, Keith; McKee, Gary
Abstract : Patients with cystic fibrosis (CF) are at increased risk of nasal polyps. We present the case of a 17-month-old Caucasian patient with CF who presented with hypertelorism causing cycloplegic astigmatism, right-sided mucoid discharge, snoring and noisy breathing. Imaging suggested bilateral mucoceles in the ethmoid sinuses. Intraoperatively, bilateral soft tissue masses were noted, and both posterior choanae were patent. Polypectomy and bilateral mega-antrostomies were performed. Histological examination revealed inflammatory nasal polyposis typical of CF. The role of early functional endoscopic sinus surgery (FESS) in children with CF nasal polyposis remains questionable as the recurrence rate is higher, and no improvement in pulmonary function has been shown. Our case, however, clearly demonstrates the beneficial upper airway symptom relief and normalisation of facial appearance following FESS in a child with this condition.